The effect of a structured programme to increase patient activity during inpatient stroke rehabilitation: a Phase I cohort study. (February 2016) - Tyson, SF; Burton, L; McGovern, A
Objective: To develop an intervention and undertake a proof-of-concept evaluation of its feasibility, acceptability, and impact on recorded patient activity levels during inpatient stroke rehabilitation. Design: A longitudinal cohort design. Setting: Three inpatient stroke rehabilitation services. Subjects: Stroke survivors receiving inpatient rehabilitation. Intervention: A programme designed to increase patient activity, including individualised patient timetables, independent practice, therapeutic group work, and structured social activities was developed and implemented without additional resource. Main measures: Patients' recorded activity levels were compared for two weeks before and after implementation of the programme. Data regarding the estimated time spent in different types of activity were extracted from patient treatment records, patients' and therapists' diaries, or timetables (if used) to measure patient activity levels Results: At baseline, recorded activity levels were low; patients undertook a mean of 61 minutes (SD = 39) of activity per day. After implementation of the programme, recorded activity levels significantly increased to a mean of 123 minutes (SD = 88) per day ( p = 0.0001). The time spent in all types of recorded activity increased ( p = 0.0001–0.002), except psychology where the increase did not reach significance ( p = 0.670). Conclusions: A structured programme can significantly increase recorded patient activity levels during inpatient stroke rehabilitation without additional resource.